Investigation of metabolic crosstalk between host and pathogenic Clostridioides difficile via multiomics approaches - Kwon, Ji-Eun; Jo, Sung-Hyun; Song, Won-Suk; Lee, Jae-Seung; Jeon, Hyo-Jin; Park, Ji-Hyeon; Kim, Ye-Rim; Baek, Ji-Hyun; Kim, Min-Gyu; Kwon, Seo-Young; Kim, Jae-Seok; Yang, Yung-Hun; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Clostridioides difficile is a gram-positive anaerobic bacterium that causes antibiotic-associated infections in the gut. C. difficile infection develops in the intestine of a host with an imbalance of the intestinal microbiota and, in severe cases, can lead to toxic megacolon, intestinal perforation, and even death. Despite its severity and importance, however, the lack of a model to understand host-pathogen interactions and the lack of research results on host cell effects and response mechanisms under C. difficile infection remain limited. Here, we developed an in vitro anaerobic-aerobic C. difficile infection model that enables direct interaction between human gut epithelial cells and C. difficile through the Mimetic Intestinal Host–Microbe Interaction Coculture System. Additionally, an integrative multiomics approach was applied to investigate the biological changes and response mechanisms of host cells caused by C. difficile in the early stage of infection. The C. difficile infection model was validated through the induction of disaggregation of the actin filaments and disruption of the intestinal epithelial barrier as the toxin-mediated phenotypes progressed in accordance with infection progression. In addition, an upregulation of stress-induced chaperones and an increase in the ubiquitin proteasomal pathway were identified in response to protein stress that occurred in the early stage of infection, and downregulation of proteins contained in the electron transfer chain and ATP synthase was observed. It has been demonstrated that host cell energy metabolism is inhibited through glycolysis of Caco-2 cells and reduction of metabolites belonging to the TCA cycle. Taken together, our C. difficile infection model suggests a new biological response pathway in the host cell induced by C. difficile during the early stage of infection at the molecular level under anaerobic-aerobic conditions. Therefore, this study has the potential to be applied to the development of future therapeutics through basic metabolic studies of C. difficile infection.